Usborne World History Ancient World - Fiona Chandler (U.S.A Scholastic Inc, 1999)
Surveys the history of the ancient world from the earliest farmers to the fall of the Roman Empire.
Grade 5
Keywords: History - Ancient Civilization -- History - Ancient Civilization